Capital flight to offshore and challenges of combating money «dirty» money in the modern global economy - E. N. Soloviev; A. V. Vlasov (Путеводитель предпринимателя, 2020)
This article describes the offshore as a tool for the global economy. Assessment of his scheme, scope, Offshoring economy and their impact on the national economy. Offshoring problems and threats, development of the national economy, and its method of deofshorizatsii.